Comparison of SARS-CoV-2 aerosol emission from patients with Omicron BA.1 or BA.2 subvariant infection. Issue 2 (August 2022) - Zhang, Yidun; Li, Jiaming; Jiang, Lina; Chen, Qi; Fu, Yingying; Jin, Yifei; Chen, Zehui; Tang, Fei; Zeng, Xiaohong; Wen, Huixin; Lu, Bing; Li, Li; et al.
Highlights: Both viral load in upper respiratory tract and positive rate of exhaled breath condensate from Omicron BA.2 subvariant patients were higher than those from BA.1 subvariant patients. The patients with Omicron BA.1 or BA.2 subvariant infection had the same level of virus breath emission rate, and the growth rate of BA.1 and BA.2 subvariants are similar in Caco2 cells. The viral load in upper respiratory tract and the virus breath emission rate of Omicron patients had the similar variation trend.